Cost analysis in the management of moderate-to-severe psoriasis: comparison between conventional and biological systemic therapies (Dermatology Reports, 2023)
Background. Psoriasis is a chronic inflammatory skin disease with an important socio-economic burden. Available therapies include conventional systemic drugs and biological drugs, such as Tumor Necrosis Factor (TNF)-α inhibitors, that are characterized by high costs. Aim. Perform a cost-estimation analysis of conventional treatment vs therapy with biosimilar TNF-α inhibitor between January 2021 and January 2022, according to the Apulia regional cost list. Methods. The average annual expenditure per patient on conventional treatment (cyclosporine and methotrexate) vs therapy with biosimilar TNF-α inhibitor was compared. The 'cost per responder' was determined by analyzing the percentages of 'responders' (patients achieving PASI 75 and PASI 90) and 'non-responders' (PASI